Police Barracks, Trinidad - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2010)
Exterior view of the Police Barracks building, Port of Spain, Trinidad, showing Sackville Street at right and St. Vincent Street at left. A few persons are walking on the St. Vincent Street.
Colour: Black and White; Style: Landscape: Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Police stations--Trinidad and Tobago; Public buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; Fences--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; [1920]; Hedges--Trinidad and Tobago; Children--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Hats--Trinidad and Tobago; Men--Trinidad and Tobago; Women--Trinidad and Tobago; Families--Trinidad and Tobago